What happens to others matters! An intra-individual processual approach to coworkers’ psychological contract violations - Costa, S.; Coyle-Shapiro, J. A-M. (Group and Organization Management, 2021)
Drawing on recent research highlighting the dynamic and social properties of psychological contracts, we propose a framework that examines socially embedded triggers and their impact on psychological contract change. Our model accounts for the social context in which individuals’ sensemaking process about their employment relationship occurs. The model specifies how individuals make sense of coworkers’ psychological contract violation and integrate that information into the creation of a plausible convergent or divergent account. These accounts have the potential to reinforce or initiate a review of the terms of the individual’s psychological contract schema, or they may leave the schema intact. Research and practical implications of this conceptual framework are discussed.